2016
DOI: 10.1002/14651858.cd011515.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of different imaging modalities following computed tomography (CT) scanning for assessing the resectability with curative intent in pancreatic and periampullary cancer

Abstract: Diagnostic accuracy of different imaging modalities following computed tomography (CT) scanning for assessing the resectability with curative intent in pancreatic and periampullary cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 163 publications
0
31
0
Order By: Relevance
“…3 Routine preoperative workup includes computed tomography (CT) to evaluate local resectability and to exclude disseminated disease. 4 Despite this, in approximately 10-25% of patients, locally advanced disease or occult distant metastases are identified during exploratory laparotomy. 5 Staging laparoscopy (SL) may decrease the rate of futile operations in those found to have resectable disease on CT. 5,6 SL can be combined with laparoscopic ultrasound (LUS) to allow a detection of occult liver metastases missed by preoperative CT. Due to the improvement of imaging techniques over the last decade, however, the value of LUS in addition to SL and preoperative CT may have diminished.…”
Section: Introductionmentioning
confidence: 99%
“…3 Routine preoperative workup includes computed tomography (CT) to evaluate local resectability and to exclude disseminated disease. 4 Despite this, in approximately 10-25% of patients, locally advanced disease or occult distant metastases are identified during exploratory laparotomy. 5 Staging laparoscopy (SL) may decrease the rate of futile operations in those found to have resectable disease on CT. 5,6 SL can be combined with laparoscopic ultrasound (LUS) to allow a detection of occult liver metastases missed by preoperative CT. Due to the improvement of imaging techniques over the last decade, however, the value of LUS in addition to SL and preoperative CT may have diminished.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In a recent meta-analysis, Tamburrino and colleagues [8] demonstrated that EUS is 0.87 sensitive and 0.80 specific for identifying unresectable disease in patient who were believed to have resectable pancreatic adenocarcinoma after a CT scan was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its safety, noninvasive nature, and high‐quality soft‐tissue contrast, MRI has become an important method for detecting pancreatic lesions . We previously found that the development and application of iterative decomposition of water and fat with echo asymmetry and least‐squares estimation quantitation (IDEAL‐IQ) sequences provided a useful technique for evaluating pancreatic lesions .…”
mentioning
confidence: 99%
“…Because of its safety, noninvasive nature, and high-quality soft-tissue contrast, MRI has become an important method for detecting pancreatic lesions. [11][12][13][14] We previously found that the development and application of iterative decomposition of water and fat with echo asymmetry and least-squares estimation quantitation (IDEAL-IQ) sequences provided a useful technique for evaluating pancreatic lesions. [15][16][17][18] However, thus far few studies have described a pathological comparison between the adipose component measured by the IDEAL-IQ sequence and the actual degree of fat infiltration of the pancreas in T2DM.…”
mentioning
confidence: 99%